Fracture behavior of clad pipeline containing a canoe shape surface crack subjected to large bending moment - Zhang, Yao (2020)
This paper concerns the fracture assessment of a clad pipeline subjected to large bending moment, and identifies different parameters influencing the fracture behaviors. The evolution of Crack Tip Opening Displacement (CTOD) of a pipeline containing a canoe shape crack on the external surface of the girth weld is studied under pure bending and combined pure bending and internal pressure through 3D elastic-plastic Finite Element (FE) simulations. Various parameters affecting the evolution of CTOD like crack depth, crack length to perimeter diameter ratio, internal pressure and the weld geometrical configurations have been investigated. It is observed that only the average width of the weld has a significant influence on the fracture response under pure bending, while the weld reinforcement height and fusion line slope have a moderate influence on the fracture behavior under biaxial loading. The crack at the interface between the weld and back steel has a similar fracture response to that of a crack located in the weld with equivalent effective crack depth. Finally, a strain based Failure Assessment Diagram (FAD) is proposed and compared with the fracture assessments produced by BS7910:2013, and 3D elastic-plastic FE simulations suggest that the British Standard is more conservative especially for deep cracks.